Dispelling e-myths and pre-empting disappointment: Exploring incongruities between instructors’ intentions and reality in asynchronous online discussions - Brokensha, Susan; Greyling, Willfred (South African Journal of Higher Education, 2016)
Provided that effective practices in online instructional design are met and e-myths regarding online learning are contested, asynchronous online discussions (AODs) may promote productive interaction, reflecting knowledge sharing, knowledge construction, knowledge creation or hybrids of these discourses. Within a naturalistic higher education setting, we revisited lingual data analysed in a previous study, employing Booth and Hultén’s (2003) taxonomy of pivotal contributions to online discussions to describe students’ ‘talk’ during text-based AODs. The taxonomy constituted a more comprehensive model of productive online discussion than that used in the earlier study. Contrary to our initial assumptions as novice e-instructors, functional moves were predominantly factual, while reflective and learning contributions were either uncommon or absent. In addition, participatory contributions were rare. These findings have clear pedagogical implications for the instructional design of AODs aimed at fostering productive interaction. We therefore identify design considerations that should underpin online pedagogy as it pertains to meaningful online discussion. Keywords: online instructional design, asynchronous online discussions, e-myths, knowledge sharing, knowledge construction, knowledge creation